2004
DOI: 10.1074/jbc.m313435200
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of p53 Is a Novel Mechanism for Proapoptotic Function of NF-κB

Abstract: Both pro-and antiapoptotic activities of NF-B transcription factor have been observed; however, less is known about the mechanism by which NF-B induces apoptosis. To elucidate how NF-B regulates proapoptotic signaling, we performed functional analyses using wild-type, ikk1؊/؊ , ikk2 ؊/؊ , rela ؊/؊ murine fibroblasts, MDAPanc-28/Puro, MDAPanc-28/IB␣M, and HCT116/p53 ؉/؉ and HCT116/p53 ؊/؊ cells with investigational anticancer agent doxycycline as a superoxide inducer for generating apoptotic stimulus. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 78 publications
4
93
0
Order By: Relevance
“…After 24 h of transfection, cells were fixed and stained with DAPI. Localization of p53 was monitored through red fluorescent protein, localization of IkB-DN was detected by immunofluorescent assay and nuclear DNA was visualized by DAPI staining activation (Fujioka et al, 2004). Furthermore, p53 can induce NF-kB activation via phosphorylation of RelA by ribosomal S6 kinase 1 (Bohuslav et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h of transfection, cells were fixed and stained with DAPI. Localization of p53 was monitored through red fluorescent protein, localization of IkB-DN was detected by immunofluorescent assay and nuclear DNA was visualized by DAPI staining activation (Fujioka et al, 2004). Furthermore, p53 can induce NF-kB activation via phosphorylation of RelA by ribosomal S6 kinase 1 (Bohuslav et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of NF-κB activation by SR-IκBα was found to inhibit p53-mediated apoptosis [123]. NF-κB also plays an essential role in activation of wild type p53 to initiate pro-apoptotic signaling in response to ROS accumulation [33]. This finding suggests that the inhibition of NF-κB in tumors that retain wild-type p53 may diminish, rather than augment, a therapeutic response.…”
Section: Nf-κb and The Regulation Of Apoptosismentioning
confidence: 99%
“…Moreover, we have recently reported that BD induces apoptosis in pancreatic cancer cells by activating the phosphorylation of p38-mitogenactivated protein kinase (MAPK) (Lau et al, 2009). Although the function of ROS in the activation of p38-MAPK (Yi et al, 2004;Lee et al, 2008;Chen et al, 2009), and the regulation of NF-kB activity (Hayakawa et al, 2003;Fujioka et al, 2004), has been characterised in substances-induced apoptosis in various cancer cells, the involvement of ROS in BD-induced pancreatic cancer cell apoptosis is yet to be elucidated. Given that ROS have an important function in an array of biological responses and diverse signalling pathways, we hypothesised that BD activates pro-apoptotic pathways through the enhancement of ROS production and the inhibition of NF-kB activity in pancreatic cancer cells.…”
mentioning
confidence: 99%